2005
DOI: 10.1002/cne.20641
|View full text |Cite
|
Sign up to set email alerts
|

Comparative anatomy of α2 and β adrenoceptors in the adult and developing brain of the marine teleost the red porgy (Pagrus pagrus, Sparidae): [3H]clonidine and [3H]dihydroalprenolol quantitative autoradiography and receptor subtypes immunohistochemistry

Abstract: The present study aimed to determine the anatomic distribution and developmental profile of alpha(2) and beta adrenoceptors (AR) in marine teleost brain. Alpha 2 and beta adrenoceptors were studied at different developmental stages by using [(3)H]clonidine and [(3)H]dihydroalprenolol, respectively, by means of in vitro quantitative autoradiography. Furthermore, immunohistochemical localization of the receptor subtypes was performed to determine their cellular distribution. Saturation studies determined a high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
19
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 121 publications
(188 reference statements)
14
19
0
6
Order By: Relevance
“…The adrenoceptor binding parameters support that zebrafish α 2 -and β-adrenoceptors have similar properties to those in mammals, although the Bmax values determined were lower than those in land vertebrates [38,41), but similar to those reported for the teleost Pagrus pagrus [36].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The adrenoceptor binding parameters support that zebrafish α 2 -and β-adrenoceptors have similar properties to those in mammals, although the Bmax values determined were lower than those in land vertebrates [38,41), but similar to those reported for the teleost Pagrus pagrus [36].…”
Section: Discussionsupporting
confidence: 75%
“…To label the α 2 -ARs and β-ARs, in vitro autoradiography was applied [34,35,36], using the antagonists [ 3 H]-RX821002 (for α 2 -AR; 54Ci/mol, Amersham, UK) and Following incubation, free radioligand was removed by two washes in ice-cold TrisHCl buffer (5 and 10 minutes), and then sections were dried in a cold air stream.…”
Section: Brain Adrenoceptor Autoradiographymentioning
confidence: 99%
See 1 more Smart Citation
“…, 2008). Similar distributions of ARs are found in a marine species, the red porgy, although hindbrain nuclei are not reported (Zikopoulos and Dermon, 2005).…”
Section: Th-ir Innervation Of Central Auditory Circuitry-likesupporting
confidence: 51%
“…In fact, many dopaminergic drugs (DA agonists) are relatively strong antagonists at the a 1 and/or a 2 adrenergic receptors (Hommer, Zahn, Pickar & Van Kammen 1984). Other researchers have reported that adrenergic receptors were extremely expressed in the hypothalamus, as previously suggested for teleost fish, and thus hypothalamic adrenergic receptors involved in gonadotropinreleasing control, sexual differentiation and reproductive behaviour regulation in fish (Ruuskanen, Peitsaro, Kaslin, Panula & Scheinin 2005;Zikopoulos & Dermon 2005;Ampatzis et al 2008).…”
Section: Resultsmentioning
confidence: 84%